THE SYSTEM ANALYSIS AND THE IMPROVEMENT OF THE OF ORGANIZATIONAL STRUCTURE OF THE UNIVERSITY - E. Erikenova (Вестник университета)
The article considers the possibilities of redesign of the organizational management structures in accordance with the current requirements of their construction (optimality, efficiency, reliability, flexibility, adaptability, sustainability, efficiency, etc.) to accomplish the mission and functions of universities, and to achieve their goals. Applying the latest methods of system analysis in management, the author on a number of criteria evaluates advantages and disadvantages of traditional and innovative, adaptive organizational structures of management of the modern University, more acceptable for the effective management of scientific and educational institutions.